2020
DOI: 10.1101/2020.06.15.153023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

piRNAs prevent runaway amplification of siRNAs from ribosomal RNAs and histone mRNAs

Abstract: Piwi-interacting RNAs (piRNAs) are a largely germline-specific class of small RNAs found in animals.Although piRNAs are best known for silencing transposons, they regulate many different biological processes. Here we identify a role for piRNAs in preventing runaway amplification of small interfering RNAs (siRNAs) from certain genes, including ribosomal RNAs (rRNAs) and histone mRNAs. In Caenorhabditis elegans, rRNAs and some histone mRNAs are heavily targeted by piRNAs, which facilitates their entry into an en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Do sRNAs compete for, or control each other's Ago loading? Age-dependent patterns of Ago loading of miRNAs, tRFs and rRFs in Drosophila ( 16 , 42 , 76 ) or a balance between piRNA and 22-nt rRFs seen in the nematode ( 104 ) suggest such a possibility. Are agotrons targets of sRNA or longer regulatory (and possibly competing) RNAs?…”
Section: Resultsmentioning
confidence: 99%
“…Do sRNAs compete for, or control each other's Ago loading? Age-dependent patterns of Ago loading of miRNAs, tRFs and rRFs in Drosophila ( 16 , 42 , 76 ) or a balance between piRNA and 22-nt rRFs seen in the nematode ( 104 ) suggest such a possibility. Are agotrons targets of sRNA or longer regulatory (and possibly competing) RNAs?…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, removing some WAGOs downstream of the piRNA pathway contributes to restoring the fertility of piwi mutant worms [ 80 ]. More recent studies have revealed another class of genes that also accumulate 22G‐RNAs in the absence of piRNA, the ribosomal RNA genes [ 81 , 172 ]. However, in the case of the inheritance of 22G‐RNAs antisense to the ribosomal RNAs, called antisense ribosomal siRNAs (risiRNAs), it is not clear whether they interfere with the transcription or the processing of ribosomal RNAs and how they can contribute to the sterility phenotype [ 173 , 174 , 175 ].…”
Section: Small Rna‐mediated Inheritance Of Traits In Animal Model Org...mentioning
confidence: 99%